Pentingnya Membangun Hubungan Antar Kualitas Pribadi Konselor Dan Kualitas Pribadi Konseling - Dania Isnaeni Zahrah; Menila Wati Zalukhu; Nurul Zahratunnisa; Holifah; Ira Restu Kurnia (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This research aims to explore the importance of building a relationship between the personal qualities of a counselor and the personal qualities of counseling in the context of counseling services. Through a qualitative approach, data was collected through in-depth interviews with counselors who have experience in the field of counseling. Data analysis was conducted using content analysis method. The results of the study indicate that the relationship between the personal qualities of the counselor and the personal qualities of counseling has a significant impact on the effectiveness of counseling services. The personal qualities of the counselor, such as empathy, patience, and honesty, contribute to the creation of a positive relationship with clients, which in turn enhances counseling outcomes. The implications of this research highlight the importance of developing the personal qualities of counselors through continuous training and supervision to improve the effectiveness of counseling services